The effects of lead on the gaseous exchange and photosynthetic carbon metabolism of pea seedlings - Jerzy W. Poskuta; Eugeniusz Parys; Elżbieta Romanowska (Acta Societatis Botanicorum Poloniae, 2014)
Roots of whole 3 week-old pea seedlings (Pisum sativum L.) var. "Bordi" were immersed for 24 h in solutions of lead chloride at Pb copcentrations of 200, 400, 800,12000 mg dm3. Accumulation of lead in roots was independent of the Pb concentration, whereas the accumulation of Pb in shoots was an almost linear function of the concentration of this element in the root medium. This treatment caused Pb concentration-dependent inhibition of apparent photosynthesis (APS), photorespiration (PR), 14CO2 uptake, stomatal opening and transpiration of shoots and also germination of seeds. The most sensitive to Pb contamination was CO2 exchange, then transpiration and to a lesser degree germination of seeds. Lead caused a considerable alteration of photosynthetic and photorespiratory carbon metabolism, restricted the 14C-labeling of: phosphoglycerate, ribose+ribulose, sucrose, glycolate and glycine+serine. Under conditions of C02 uptake limited by lead, an enhancement of the 14C-labeling of malate+citrate, alanine and glucose was observed.